Determining response to nitrogen of promising rice line (Oryza sativa L.) in the low country wet zone of Sri Lanka - Suseema, K.S.; Silva, C.S.D.; Dissanayaka, I. (University of Jaffna, 2021)
A field experiment was conducted during the Maha season from August 2019 to May 2020 at Regional Rice Research and Development Center, Bombuwala, Sri Lanka to investigate nitrogen response of promising rice line of Bw 12-574 compared at growth and flowering stages of that recommended rice variety (Ld 368). Growth parameters and yield components of both treatments were compared under five different nitrogen levels i.e., 0, 50, 100, 150, and 200% recommended by the Department of Agriculture. The experimental design was a Randomized Complete Block Design with three replicates. Two varieties were tested under 5 nitrogen levels. Data were analyzed by analysis variance (ANOVA) and mean separation procedure by LSD using appropriate SAS procedures. Plant height, number of productive tillers, panicle length, leaf colour intensity, and chlorophyll content of leaves in both Bw 12-574 and Ld 368 showed an increasing trend against added nitrogen. The higher nitrogen dosages were influencing the increase of flowering days. The yield parameters including length of panicle and number of grains per panicle have shown significant differences (p=0.05) between the tested line and recommended variety. However, no significant difference was observed between the tested line and recommended variety with respect to filled grain percentage and grain yield. Hence, the response to nitrogen of Bw 12 – 574 was found to be similar to the recommended variety, Ld 368. The study concludes that the same nitrogen recommendation applied for Ld 368 would be recommended for promising rice line Bw 12-574. However, further investigations are needed to confirm the findings.
Keywords: Fertilizer; Nitrogen response; Paddy yield; Parameters; Rice